Unification Church (Penyatuan Gereja) dan Penilaiannya - Mohd. Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 1995)
This article describes one of the Christian’s movement (church’s movement), its methods and its principles, i.e: Unification Church and analysing them comparatively.